2023
DOI: 10.1186/s12886-023-03010-3
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biophysical changes after upper eyelid blepharoplasty and ptosis surgery: a review

Abstract: Upper eyelid surgeries, such as blepharoplasty and ptosis correction, are commonly performed procedures worldwide. This review examines the effects of these surgeries on ocular properties and visual function. A search of the PubMed and Google Scholar databases was conducted to identify relevant articles published after 2000. The results demonstrate that the ocular and adnexal organs function as a unified visual system, with changes in one component affecting the functions of others. Eyelid surgery can alter oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Many other studies after blepharoptosis surgery have also reported the effects of this surgery on refractive corneal topographic measurements ( 6 , 17 , 22 - 28 ). In addition, before making any further decisions, it is advised to wait 3 months after blepharoplasty surgery to repeat corneal topography and refraction because post-operative eyelid edema can persist for up to 2 months after the procedure ( 6 , 20 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many other studies after blepharoptosis surgery have also reported the effects of this surgery on refractive corneal topographic measurements ( 6 , 17 , 22 - 28 ). In addition, before making any further decisions, it is advised to wait 3 months after blepharoplasty surgery to repeat corneal topography and refraction because post-operative eyelid edema can persist for up to 2 months after the procedure ( 6 , 20 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, these findings not being significant may also be related to the small sample size. In addition, some studies reported that additional factors such as higher astigmatism in the pre-operative period, severity of ptosis level, and deep superior sulcus were associated with higher corneal astigmatism changes in the postoperative period ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation